Predictors and early outcome of hemorrhagic transformation after acute ischemic stroke - Kablau, Micha; Kreisel, Stefan H.; Sauer, Tamara; Binder, Johannes; Szabo, Kristina; Hennerici, Michael G.; Kern, Rolf (Cerebrovascular diseases, 2011)
Background: Hemorrhagic transformation (HT) after acute ischemic stroke is frequently detected using magnetic resonance imaging (MRI), in particular in patients treated with tissue plasminogen activator (tPA). Knowledge about causes and early clinical consequences of HT mostly arises from computed tomography-based studies. We analyzed potential predictors and early outcome of HT after stroke detected by MRI with T2*-weighted gradient echo sequences (T2*-MRI). Methods: 122 consecutive stroke patients (mean age 65.5 years, 41% women) who underwent T2*-MRI within 6-60 h after stroke onset were included. 25.4% of patients were treated with tPA; the overall detection rate of HT on T2*-MRI was 20.5%. Potential predictors of HT, such as age, sex, blood pressure, stroke etiology, prior antithrombotic medication, neurological deficit on admission, tPA treatment, and specific MRI findings, were analyzed. In addition, we evaluated the effect of HT on early outcome: a decrease of >4 points on the National Institute of Health Stroke Scale (NIHSS) on day 5 was considered early improvement, and an increase of >4 points was considered early deterioration. Results: The main predictor for occurrence of HT was tPA treatment (48.4 vs. 11.1%; odds ratio 7.50; 95% confidence interval 2.9-19.7; p < 0.001). Furthermore, the development of HT was associated with a severer neurological deficit on admission (mean NIHSS score 9.9 vs. 5.9; p = 0.003), and territorial infarction (88 vs. 58.8%; p = 0.007). 19 patients (15.6%) showed early improvement which was associated with the occurrence of HT (p = 0.011) and tPA treatment (p < 0.001). Conclusions: HT is a frequent finding on T2*-MRI in patients with acute ischemic stroke associated with tPA treatment, territorial infarction and severer neurological deficits on admission. However, HT does not cause clinical deterioration; it is rather related to a favorable early outcome likely reflecting early recanalization and better reperfusion in these patients.